Maternal dissatisfaction with their children's body size in private schools in the Federal District, Brazil - Pedroso, Jéssica (2018)
We investigated the prevalence of maternal dissatisfaction with their child's body size and its associated factors among mothers of first- to third-grade elementary school students in private schools in the Federal District, Brazil. This is a cross-sectional study with 548 mother-schoolchildren pairs. We measured children's weight and height, and collected their mother's sociodemographic data and Body Mass Index using an online questionnaire. We also verified maternal body dissatisfaction and maternal dissatisfaction with their child's body size using Shape Scales. Most mothers (50.5%) were dissatisfied with their child's body size. Mothers of boys (Adjusted OR = 2.85) were more likely to want a larger silhouette for their child, while mothers of girls (Adjusted OR = 3.18), overweight (Adjusted OR = 24.83) and obese (Adjusted OR = 189.86) children were more likely to want a thinner silhouette for their child. A positive correlation was observed between maternal dissatisfaction with their own body and maternal dissatisfaction with their children's body size (rs = 0.178). There was a high prevalence of maternal dissatisfaction with their child's body size, particularly among mothers of overweight and obese children. Additional studies should be conducted to better understand the influence of this dissatisfaction on maternal practices and attitudes related to their child's body, food consumption, and lifestyle.